The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fphar.2019.00561
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Toxicology Data Resources to Support Read-Across and (Q)SAR

Abstract: A plethora of databases exist online that can assist in in silico chemical or drug safety assessment. However, a systematic review and grouping of databases, based on purpose and information content, consolidated in a single source, has been lacking. To resolve this issue, this review provides a comprehensive listing of the key in silico data resources relevant to: chemical identity and properties, drug action, toxicology (including nano-material toxicity), exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 198 publications
(185 reference statements)
0
45
0
Order By: Relevance
“…In a recent comprehensive review, over 900 databases were identified and characterised in terms of the type of information available, as well as their public or commercial accessibility, interoperability, search criteria, etc. 17 The categories for the types of database considered (with the number of associated databases given in parentheses) were: biological (268); drug discovery (157); clinical trials (116); chemistry (80); omics (60); toxicology (57); protein-protein interactions (54); alternative methods (39); ADME (38); pathways (38); environmental exposure (30); nanomaterials toxicity (22); and patents (9). Of the hundreds of databases available, some representative examples of freely accessible databases are shown in Table 2, in order to indicate the nature and scope of these resources.…”
Section: Databasesmentioning
confidence: 99%
“…In a recent comprehensive review, over 900 databases were identified and characterised in terms of the type of information available, as well as their public or commercial accessibility, interoperability, search criteria, etc. 17 The categories for the types of database considered (with the number of associated databases given in parentheses) were: biological (268); drug discovery (157); clinical trials (116); chemistry (80); omics (60); toxicology (57); protein-protein interactions (54); alternative methods (39); ADME (38); pathways (38); environmental exposure (30); nanomaterials toxicity (22); and patents (9). Of the hundreds of databases available, some representative examples of freely accessible databases are shown in Table 2, in order to indicate the nature and scope of these resources.…”
Section: Databasesmentioning
confidence: 99%
“…Therefore, as part of an effort to expand the toxicology database, a multidimensional HTS assay was devised to examine all ToxCast phase 1 and 2 chemicals (over 1,000 unique chemicals) for developmental-and neuro-toxicity in the embryonic zebrafish [7]. While computational approaches to bridge the data gap above have been developed, with Quantitative Structure-Activity Relationship (QSAR) and Read-Across being the most commonly used methodologies [8][9][10][11][12][13]. Both methods rely on the grouping of chemicals together using fragment descriptors, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The good news is that with “big data” a manifold of data sources is available to guide read‐across. Recently, Pawar et al conducted a meta‐review identifying more than 900 databases that contain data relevant for read‐across …”
Section: Expert Methodsmentioning
confidence: 99%
“…Recently, Pawar et al conducted a meta-review identifying more than 900 databases that contain data relevant for read-across. 36 Several recent case studies demonstrated that a careful read-across can be utilized to estimate the toxicities of various compound classes. [37][38][39][40][41] However, all case-studies show that the approach is highly dependent on the available data and the definition of similarity between the parent compound and the analogs.…”
Section: Read-acrossmentioning
confidence: 99%